Prevalence and Diagnosis of Diabetic Cardiovascular Autonomic Neuropathy in Beijing, China: A Retrospective Multicenter Clinical Study - Pan, Qi; Li, Quanmin; Deng, Wei; Zhao, Dong; Qi, Lin; Huang, Wei; Ma, Li; Li, Hongmei; Li, Yufeng; Lyu, Xiaofeng; Wang, Aihong; Yao, Hebin; et al. (Frontiers in Neuroscience, 2019)
Cardiovascular autonomic neuropathy (CAN) is a debilitating condition occurring among diabetic patients especially those with long duration of disease. Whereas incidences and treatment of CAN has been well described for Western populations, fewer studies have been conducted among the Chinese. This study, therefore, aimed to assess the prevalence of CAN among sampled Chinese diabetic patients. Accordingly, 2,048 participants with a history of type 1 diabetes mellitus (T1DM, 73) and type 2 diabetes mellitus (T2DM, 1975) were randomly sampled from 13 hospitals. Patients’ biodata were recorded, and autonomic nervous system function tests performed to aid in the preliminary diagnosis of CAN. The final CAN diagnosis was based on the Ewing's test in which heart rate variation (HRV) values were evaluated through deep-breathing (DB), lying-to-standing (LS) and Valsalva (V) tests. Systolic blood pressure (SBP) variation values were also evaluated through LS. In the T1DM group, 61.6% patients were diagnosed with CAN and no differences were observed in the baseline and clinical data between this group and those without CAN (P>0.05). In the T2DM group, 62.6% patients were diagnosed with CAN and statistically significant differences were found between the CAN and non- CAN group with regards to age, duration of diabetes, metformin treatment, retinopathy and hypertension history (P<0.05). The most common manifestations of CAN included weakness (28.6%), dizziness (23.4%), frequent urination (19.6%), upper body sweating (18.3%) and nocturia (15.9%). Additionally, duration of disease and age were independent risk factors for CAN in T1DM and T2DM, respectively. On diagnosis, a combination of the V test + LS test provided the highest sensitivity of detecting CAN among T1DM group (sensitivity=97.6%, AUC=0.887) while for T2DM category, DB test had the highest sensitivity (83.6%), and maximal AUC (0.856) was found with V test + DB test. The overall prevalence of diabetes with CAN in the study was up to 63%.